Seismotectonic characterization of Mexico - Cotilla-Rodríguez, Mario Octavio (2019)
Mexico is an active seismotectonic region mainly sitting on the continental plate of North America and has two types of seismicity: interplate and interior plate.  The hierarchical structure embraces 3 seismotectonic provinces (north-western, western and central-eastern), comprised of 11 seismotectonic units wherein seismogenetic zones are located. The latter are segmented. The western province shows the highest level of seismicity and is the area where convergent plates make contact.